Acute effects from the half-squat performed using a repetition versus differential approach in youth soccer players - Coutinho, D.; Abade, E.; Gonçalves, B.; Santos, S.; Schöllhorn, W.; Sampaio, J. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Over the last years there have been a wide body of research exploring the best strategies to promote acute enhancements in players` performance. Despite that, most studies have been focused on adult and elite players, and different results may be identified when considering players from lower levels of performance and belonging to youth categories. In addition, most studies conducted in this domain focused in repetitive movement patterns, and while adding variability has been considered as a useful approach to enhance players` performance at short and long-term perspectives, less is known regarding it applicability to acute enhance players physical performance. Therefore, this study aimed to compare the acute enhancement effects of performing the half-squat in a flywheel ergometer between a more-repetitive approach (low noise) and a more variable approach (differential learning, high noise) in youth soccer players.